A Backstepping Based Pid Controller for Stabilizing an Underactuated X4-AUV - Nur Fadzillah, Harun; Zainah, Md. Zain (2015)
The autonomous underwater vehicle (AUV) mostly has fewer control inputs than the degree of freedoms (DOFs) in motion and be classified into underactuated system. It is difficult tasks to stabilize that system because of the highly nonlinear dynamic and model uncertainties. Hence, it usually required nonlinear control method and this paper presents the stabilization of an underactuated X4-AUV using backstepping based PID nonlinear control techniques. The X4-AUV system is executed by separating system into two parts subsystem which is translational and rotational subsystems. Integral backstepping control is applied for translational subsystem and PID backstepping control for the rotational subsystem. The effectiveness of the proposed control technique for an underactuated X4-AUV demonstrates through simulation.